2017
DOI: 10.1093/pasj/psx092
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of galaxy overdensity around quasar pairs at z < 3.6 based on the Hyper Suprime-Cam Subaru Strategic Program Survey

Abstract: We investigate the galaxy overdensity around proto-cluster scale quasar pairs at high (z > 3) and low (z ∼ 1) redshift based on the unprecedentedly wide and deep optical survey of the Hyper Suprime-Cam Subaru Strategic Program (HSC-SSP). Using the first-year survey data covering effectively ∼ 121 deg 2 with the 5σ depth of i ∼ 26.4 and the SDSS DR12Q catalog, we find two luminous pairs at z ∼ 3.3 and 3.6 which reside in > 5σ overdense regions of gdropout galaxies at i < 25. The projected separations of the two… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…Using the Hyper-Suprime-Cam survey and SDSS DR12 QSO database, Onoue et al (2018) found that QSO pairs trace >5σ overdense regions over 15 co-Mpc. These overdense regions could be protoclusters with M z=0 >10 14 M e .…”
Section: The Association Of Cool Gas Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the Hyper-Suprime-Cam survey and SDSS DR12 QSO database, Onoue et al (2018) found that QSO pairs trace >5σ overdense regions over 15 co-Mpc. These overdense regions could be protoclusters with M z=0 >10 14 M e .…”
Section: The Association Of Cool Gas Andmentioning
confidence: 99%
“…This has motivated our survey using QSO pairs. In addition, recent studies have suggested that Sloan Digital Sky Survey (SDSS) QSO pairs trace protoclusters (Onoue et al 2018), and thus the extended Lyα, C IV, He II lines traced by QSO pairs can be used to probe cool (T ∼ 10 4 K) and warm (T ∼ 10 5 K) gas in the early intracluster medium (ICM; Valentino et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Several observations support this hypothesis (e.g. Kim et al 2009;Cantalupo et al 2012;Morselli et al 2014;Ota et al 2018;Onoue et al 2018) although some exceptions have been found (Bañados et al 2013;Fanidakis et al 2013;Mazzucchelli et al 2017). In practice, we consider each DM halo as a potential host of a QSO and sample the associated magnitude at 1450 Å (M AB ) from a Gaussian distribution with mean…”
Section: Ionizing Sourcesmentioning
confidence: 99%
“…(2019b)), Hydrogen Alpha Emitters (HAEs) (Hatch et al, 2011b;Hayashi et al, 2012), submillimeter galaxies (Daddi et al, 2009;Capak et al, 2011;Rigby et al, 2014;Dannerbauer et al, 2014), radio galaxies (Venemans et al, 2002(Venemans et al, , 2007Hatch et al, 2011a;Hayashi et al, 2012;Wylezalek et al, 2013;Cooke et al, 2014), isolated QSOs González-Serrano, 1999, 2002;Stott et al, 2020) and systems of QSOs (Boris et al, 2007;Onoue et al, 2018). These are all biased tracers and are useful to find massive systems in formation (Overzier, 2016), since the bias between the distribution of baryonic matter and dark matter haloes in structure formation scenarios (Kaiser, 1984) implies that high-z objects form in large high-z density fluctuations.…”
Section: Biased Tracers Of Protoclustersmentioning
confidence: 99%
“…Recently, Stott et al (2020) to protoclusters and others, not (e.g., Boris et al, 2007;Farina et al, 2011;Green et al, 2011;Sandrinelli et al, 2014;Eftekharzadeh et al, 2017;Onoue et al, 2018).…”
Section: Isolated and Systems Of Quasarsmentioning
confidence: 99%